Instructional leadership practices in under-enrolled rural schools in Miri, Sarawak / Andy Fred and Gurcharan Singh Bishen Singh - Fred, Andy; Bishen Singh, Gurcharan Singh (Universiti Teknologi MARA, 2021)
This study focuses on teachers’ perceptions of their headmasters’ instructional leadership practices in under-enrolled rural schools of Sarawak, Malaysia. It also focuses on the issues and challenges faced by the headmasters in practicing instructional leadership roles as demanded by the Malaysia Education Blueprint 2013-2025. The mixed method research employed the Instructional Leadership Model by Hal linger and Murphy (1985). The quantitative data was collected through a survey method using ‘The Principal Instructional Management Rating Scale (PIMRS) adapted from Hallinger (2008) and analysed using descriptive and inferential statistics with SPSS IBM Version 22.0 software. The qualitative data from interviews were coded thematically and analysed to support the survey results. The study found the level of the headmasters’ instructional leadership in the three dimensions as “medium high” (mean = 3.57, SD = 0.90). There is a statistically significant difference between male and female teachers’ perceptions regarding their headmasters’ instructional leadership practices. This study also revealed the headmasters’ instructional leadership practices as “medium high” level among under-enrolled rural schools. However, the issues and challenges faced by the schools made it more difficult for them to improve their academic qualities.